How do you solve for y in ##Ax – By = C##?

##y=(-C+Ax)/B##

We begin with ##Ax-By=C##. Our goal is to isolate ##y##, and the step I would do is to subtract ##Ax## on both sides. If we do that, we have ##-By=C-Ax##. From here we need to undo the ##-B*y##, so we should divide by ##-B##. Now, I like to break this up into two steps just so I don’t make any silly mistakes. So first I divide by ##-1## on both sides, which gives us ##By=(C-Ax)/-1## or ##Bx=-C+Ax##. Now I just divide by ##B## on both sides, which leaves us with ##y=(-C+Ax)/B##.

Leave a Reply

Your email address will not be published. Required fields are marked *